Pertumbuhan Tanaman Kacang Tanah (Arachis hypogaea L.) pada Tanah Gambut yang Diaplikasikan dengan Bokashi Jerami dan Pupuk Petrhikaphos - Tri Rima Setyawati, Syukmaya Ramadani, Riza Linda (Jurnal Protobiont, 2015)
The low fertility and high soil acidity make the peat soils require processing before being used as a medium for plant growth. Peat soil improvement efforts need to be done on an ongoing basis. This study aims to determine the effect and the optimal dose on the using of bokashi straw and petrhikaphos fertilizer on the peanut plant growth (Arachis hypogaea). This study used Factorial Completely Randomized Design (FCRD) with 2 factors namely petrhikaphos fertilizer (A) and bokashi straw (B). Each factor consists of 4 levels, they are: control, 5g; 15g and 25g for petrhikaphos fertilizer and control, 18,75g; 37,5g and 56,25gfor bokashi straw fertilizer. The findings of the research showed that the using of bokashi fertilizer up to 56,25g dosage /plant has not been able to give a noticeable effect on the growth and yield of peanut crop production. Based on those four-doseÂ  treatments which were given, the dose of 25g /kg of seed showed the best result for the parameter root dry weight, number of pods, seeds, seed weight, number of nodules and the total number of effective root nodules. There were no interactions between bokashi and petrhikaphos fertilizer on to allÂ  observations A. hypogaea growth.